The chain mediating roles of anxiety and depression in the relationship between the effects of the COVID-19 pandemic and procrastination in adolescents: a longitudinal study - Zhengxue Qiao; Yongmei Wu; Yunjia Xie; Xiaohui Qiu; Lu Chen; Jiarun Yang; Hui Pan; Simeng Gu; Xiuxian Yang; Xiaomeng Hu; Ping Wei; Jinxin Zhao; et al. (BMC, 2023)
Abstract Background The relationship between the Coronavirus Disease 2019 (COVID-19) pandemic, which is a traumatic event for adolescents, and procrastination is not clear. Mental health may play an important role in this relationship; however, the underlying mechanisms remain unknown. This study aimed to construct chain mediation models to examine whether anxiety and depression symptoms mediate the effects of the COVID-19 pandemic on procrastination in adolescents. Methods A convenience sample of 12 middle and high schools in Harbin, China, with four follow-up online surveys was conducted during the COVID-19 pandemic. A total of 4,156 Chinese adolescents were enrolled in this study, of whom ages 11-18 (Mean = 13.55; SD = 1.18), 50.75% were male, and 93.24% were middle school students. Descriptive demographic analysis and Pearson's correlation analysis of the effects of the COVID-19 pandemic (T1), anxiety(T2), depression (T3), and procrastination (T4) were performed in SPSS 22.0. Chain mediation analysis performed with Mplus 8.3. Results The effects of the COVID-19 pandemic, anxiety symptoms, depression symptoms, and procrastination were positively correlated (P < 0.01). The effects of the COVID-19 pandemic have a direct link on adolescent procrastination (effect = 0.156; SE = 0.031; 95%CI: 0.092, 0.214), and have three indirect paths on procrastination: the independent mediating role of anxiety symptoms was 29.01% (effect = 0.047; SE = 0.012; 95%CI: 0.024, 0.072), the independent mediating role of depression symptoms was 29.01% (effect = 0.047; SE = 0.010; 95%CI: 0.030, 0.068), as well as the completely chain mediating role of anxiety and depression symptoms was 15.43% (effect = 0.025; SE = 0.005; 95%CI: 0.017, 0.036). Conclusions Our results suggest that anxiety and depressive symptoms are part of a causal chain between the effects of the COVID-19 pandemic and procrastination among Chinese adolescents. To effectively reduce their procrastination, attention should be paid to the emotional distress caused to adolescents by major events such as the COVID-19 epidemic. All data were taken from self-reported measures and one city in China, which may bias the results and limit their generalizability.